Upaya Menjaga Kesehatan Mental Ibu Hamil melalui Peningkatan Pengetahuan dan Keterampilan di Masa Pandemi Covid-19 - Sudirman, Jumrah; Rahayu Eryanti K.; Fadjriah Ohorella (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
This effort to maintain the mental health of pregnant women is a form of activity during the COVID-19 pandemic to help pregnant women have mental readiness to face childbirth by increasing knowledge and skills and reducing maternal stress. This activity is carried out in the form of providing education and therapeutic exercises to reduce stress. The activity lasted for 6 months which was carried out through class sessions and home visits to respondents. The results of the activity showed that there was an average increase in respondents' knowledge of 24.96%, 24 respondents who experienced a decrease in post-activity stress and 34 people (80.95%) who were skilled at doing the therapy that was taught. Further programs are needed to ensure the mental health of pregnant women so that they are not only physically healthy but also mentally healthy.